Depressive Symptomatology and Activities of Daily Living in Idiopathic Parkinson's Disease without Dementia. Preliminary data from a new scale specifically to assess depression in Parkinson's disease ESDEPARK (2024)
To study the influence of depressive symptomatology on Activities of Daily Living (ADLs instrumental and advanced) in patients with Idiopathic Parkinson's Disease without Dementia (IPD without Dementia) on Hoehn and Yahr stage I and II, through a scale that aims to measure depressive symptomatology specifically in Parkinson's Disease (PD). Depression is the most frequent neurobehavioral or emotional alteration in IPD without Dementia, and is related to alterations in patients' basic, instrumental and advanced activities of daily living contributing to a worsening in their quality of life.